Spiritual art of Natal - Leeb - du Toit, Juliette (Pietermaritsburg : Tatham Art Gallery, 1993)
Bhengu, Gerard ; Cormick, Dina ; Custodis, Sr Gereon ; Dhlomo, Bongiwe ; Dikgale, Noah ; Dlamini, J. ; Gcwensa, Bernard M. ; Gumede, G.S. ; Gumede, Jackson ; Madela, Laduma ; Mbatha, Azaria ; etc.
Spiritual art of Natal, Tatham Art Gallery, Pietermaritsburg, 1993
boek
Keywords: Zuid-Afrika